Enhanced immune response to pneumococcal infection in malnourished mice nasally treated with heat-killed Lactobacillus casei - Villena, Julio Cesar (2009)
The present study analyzed whether nasal administration of viable and non-viable Lactobacillus casei CRL 431 to immunocompromised mice was capable of increasing resistance against Streptococcus pneumoniae. Weaned micewere malnourished after consuming a PFD for 21 days. Malnourished micewere fed a BCD for 7 days or BCD for 7 days with viable or non-viable L. casei nasal treatments on day 6 and day 7 (BCD+LcV and BCD+LcN, respectively). The MNC group received PFD whereas the WNC mice consumed BCD. MNC mice showed greater lung colonization, more severe lung injuries, impaired leukocyte recruitment and reduced antibodies and cytokine production when compared with WNC mice. Administration of L. casei increased the resistance of malnourished mice to the infection. Both BCD+LcV and BCD+LcN treatments prevented the dissemination of the pathogen to the blood and induced its lung clearance. BCD+LcVor BCD+LcN groups showed improved production of TNF-? and activity of phagocytes in the respiratory tract, an effect that was not observed in the BCD control group. In addition, IL-4 and IL-10 were significantly increased in BCD+LcV and BCD+LcN groups, which correlated with the increase in the levels of specific respiratory IgA. The nasal treatments with L. casei were also effective at stimulating the production of specific IgG at both the systemic and the respiratory levels. The comparative study between the viable and the non-viable bacteria demonstrated that viability would be an important factor to achievemaximumprotective effects.However, the results fromthis study suggest that heat-killed lactic acid bacteria are also effective in the immunomodulation of the systemic and respiratory immune system.